(untitled) (Medicine Today, 2020)
Introduction: Spinal tubercular infection is the most common and dangerous form of skeletal tuberculosis. Transpedicular instrumentation systems have distinct advantages such as rigid segmental fixation, stabilization of the three column of the spine, least failure at bone metal interface, early post-operative mobilization with efficient nursing care and least complications in the management of tuberculosis of the thoraco-lumbar spine. Objectives was to evaluate the outcome of decompression and transpedicular screw fixation in the management of tuberculosis of the thoracolumbar spine. Materials and Methods: An observational follow-up study. A total no. of 21 patients aged between 19-72 years and both sexes (Male-9, Female-12) was included in the study. Patients diagnosed as tuberculosis of the thoraco-lumbar spine were operated by direct decompression, transpedicular screw fixation and fusion with bone graft and mesh cage in some cases. First follow-up at 1 month after operation and thereafter at 3 and 6 months follow-up was done. Results: This study shows mean±SD age was 40±11.29 years. 57.1% were female and 42.9% were male. Lesion 66.7% were dorsal, 19.0% were lumbar and 14.3% were dorsolumbar. 42.86% were ASIA grade C, 33.33% were ASIA grade D, 9.52% were both ASIA grade B & E and 4.76% were ASIA grade A in preoperative stage. On the other hand in postoperative 61.90% were ASIA grade E, 33.33% were ASIA grade D and 4.76% were ASIA grade B. The difference was statistically significant (P<0.001). Four-fifths (80.95) of the patients had excellent outcome followed by 14.29% good outcome, 4.76% fair and 0% poor outcome. Conclusions: Posterior approach is a minimum surgical intervention that encourages neurological recovery. Medicine Today 2020 Vol.32(2): 104-111